Benchmarking coherent errors in controlled-phase gates due to spectator qubits - Krinner, S.; Lazar, S.; Remm, Ants; Andersen, C. K.; Lacroix, N.; Norris, G. J.; Hellings, Christoph; Gabureac, M.; Wallraff, A.; Eichler, Christopher (Physical Review Applied, 2020)
A major challenge in operating multiqubit quantum processors is to mitigate multiqubit coherent errors. For superconducting circuits, besides crosstalk originating from imperfect isolation of control lines, dispersive coupling between qubits is a major source of multiqubit coherent errors. We benchmark phase errors in a controlled-phase gate due to dispersive coupling of either of the qubits involved in the gate to one or more spectator qubits. We measure the associated gate infidelity using quantum-process tomography. We point out that, due to coupling of the gate qubits to a noncomputational state during the gate, two-qubit conditional-phase errors are enhanced. Our work is important for understanding limits to the fidelity of two-qubit gates with finite on-off ratio in multiqubit settings.
CRIS-Team Scopus Importer:2022-06-27